Cementing material for high-water-content sludge and preparation method thereof

By using cementitious material formulas of silicate cement, lime, fly ash and other components in high moisture content sludge, the problems of sludge dehydration and curing strength are solved, and the resource utilization and pollution reduction of sludge are achieved.

CN119528530AActive Publication Date: 2025-02-28FOSHAN TRANSPORTATION SCI & TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411529983.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

How to quickly dehydrate and improve the curing strength of high-water content silt, realize the resource utilization of dredged silt and reduce pollution.

Method used

The mechanical properties and compactness of the sludge are improved through hydration reaction and modification treatment.

Benefits of technology

The rapid dehydration and high curing strength of sludge with high moisture content are achieved, which promotes the resource utilization of sludge and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a cementing material for high-water-content sludge. The cementing material comprises the following components in parts by weight: 25-40 parts of Portland cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquid, 10-25 parts of bentonite and 0.5-4 parts of an anti-dispersing agent. The prepared cementing material for the high-water-content sludge can rapidly dehydrate the high-water-content sludge, the curing strength of the high-water-content sludge is improved, resource utilization of dredged sludge is achieved, and pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cementitious materials, and in particular to a cementitious material for high-water content sludge and a preparation method thereof. Background Art

[0002] There are many rivers and lakes in my country. With the rapid development of shipping, rivers and lakes must be dredged regularly to ensure smooth shipping and reduce the pollution of water resources by sediment. The main methods of dredged sludge treatment are ocean filling and land filling. However, ocean filling will cause pollution to the marine environment, and land filling will lead to waste of land resources and secondary pollution. Therefore, how to properly dispose of dredged sludge is a problem that needs to be solved urgently. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a binder material for high-water content sludge, which can quickly dehydrate the high-water content sludge, improve its solidification strength, realize the resource utilization of dredged sludge and reduce pollution.

[0004] The technical problem to be solved by the present invention is also to provide a method for preparing a binder material for high-water content sludge, wherein the preparation method is simple and does not require complicated processing conditions.

[0005] In order to solve the above problems, the present invention provides a binder material for high-water content sludge, which includes the following components in parts by weight: 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite, and 0.5-4 parts of anti-dispersant.

[0006] In some embodiments, the anti-dispersion agent includes polyacrylamide and sodium polyacrylate.

[0007] In some embodiments, the mass ratio of the polyacrylamide to the sodium polyacrylate is (1-2):1.

[0008] In some embodiments, the bentonite is sodium bentonite; and the polyacrylamide is anionic polyacrylamide.

[0009] In some embodiments, the mass ratio of the bentonite to the anti-dispersant is (4-5):1.

[0010] In some embodiments, the modified papermaking black liquor is prepared by the following method:

[0011] Evaporating and concentrating papermaking black liquor to obtain high-concentration papermaking black liquor;

[0012] Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 140°C to 160°C for 0.5h to 1h to obtain modified papermaking black liquor.

[0013] In some embodiments, the papermaking black liquor is papermaking black liquor produced during alkaline pulping;

[0014] The concentration of the high-concentration papermaking black liquor is 60% to 70%.

[0015] In some embodiments, the strength grade of the silicate cement is not less than 42.5;

[0016] The lime is quicklime, and the effective CaO content is not less than 85%;

[0017] The fly ash is Class II fly ash.

[0018] To solve the above problems, the present invention also provides a method for preparing a binder for high-water content sludge. By weight, 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite and 0.5-4 parts of anti-dispersant are mixed to obtain a binder for high-water content sludge.

[0019] And the application of the above-mentioned cementing material for high-water content sludge in the solidification of high-water content sludge.

[0020] The implementation of the present invention has the following beneficial effects:

[0021] The present invention introduces silicate cement and lime into the formula, which can generate strength through hydration reaction and improve the mechanical properties of sludge. At the same time, fly ash is added to accelerate its hydration and generate strength in the alkaline environment created by silicate cement and lime, and fly ash has volcanic ash effect and micro-aggregate effect, which can fill the pores of sludge and improve the compactness. In addition, bentonite, anti-dispersant and modified papermaking black liquor are added to the formula of the present invention. Bentonite can be used as a part of the cementitious material to hydrate and form strength. It can absorb free water molecules and reduce the attenuation of the hydration strength of the solidified material due to excessive water content; the addition of anti-dispersant is conducive to strengthening the connection between the material and the sludge, blocking excess free water, accelerating the dehydration of the sludge, and improving the solidification strength of the cementitious material to the sludge particles; the modified papermaking black liquor makes the raw materials of the cementitious material disperse more evenly and increases the solidification strength of the cementitious material. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. In addition, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0023] In the description of the present invention, it is necessary to understand that the terms "length", "width", "up", "down", "left", "right", "horizontal", "top", "bottom", etc., indicating directions or positional relationships, are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0025] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0026] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0027] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the examples of various specific processes and materials provided by the present invention, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.

[0028] In the present invention, "preferred" and "better" are only used to describe implementation methods or embodiments with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features. In the present invention, when involving numerical ranges, unless otherwise specified, the two endpoints of the numerical range are included.

[0029] The invention provides a cementing material for high-water content sludge, which comprises the following components by weight: 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite and 0.5-4 parts of anti-dispersant.

[0030] The present invention introduces silicate cement and lime into the formula, which can generate strength through hydration reaction and improve the mechanical properties of sludge. At the same time, fly ash is added to accelerate its hydration and generate strength in the alkaline environment created by silicate cement and lime, and fly ash has volcanic ash effect and micro-aggregate effect, which can fill the pores of sludge and improve compactness. In addition, bentonite and anti-dispersant are added to the formula of the present invention. Bentonite can be used as a part of the cementitious material to hydrate and form strength. It can absorb free water molecules and reduce the attenuation of the hydration strength of the solidified material due to excessive water content. The addition of anti-dispersant is beneficial to strengthen the connection between the material and the sludge, block excess free water, accelerate the dehydration of the sludge, and improve the solidification strength of the cementitious material to the sludge particles.

[0031] Specifically, silicate cement can be hydrated to form strength. In some embodiments, the strength grade of the silicate cement is not less than 42.5. Exemplary weight parts of the silicate cement are 25 parts, 30 parts, 35 parts, and 40 parts, not limited to the above.

[0032] Lime can absorb a large amount of water, and the hydration reaction forms strength, and creates an alkaline environment to promote the hydration of other materials and chemical reactions. In some embodiments, the lime is quicklime, and the effective CaO content is not less than 85%. The exemplary weight parts of the lime are 30 parts, 35 parts, 40 parts, and 45 parts, which are not limited to the above.

[0033] As a part of cementitious materials, fly ash has micro-aggregate effect and volcanic ash effect, which can enhance the solidification density of sludge and generate strength by hydration reaction in the alkaline environment created by cement lime. In some embodiments, fly ash is grade II fly ash. Exemplary weight parts of the lime are 15 parts, 20 parts, 25 parts, and 30 parts, which are not limited to the above.

[0034] Bentonite can also be used as a part of cementitious materials, participate in hydration reaction to form strength, and at the same time, it has good water absorption and can absorb excess free water in high-water content sludge, thereby improving the overall hydration strength of the cementitious materials. The exemplary weight parts of the bentonite are 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, and 24 parts, but are not limited to the above.

[0035] In some embodiments, the anti-dispersion agent includes polyacrylamide and sodium polyacrylate. The incorporation of polyacrylamide is conducive to strengthening the bonding effect between the solidifying material and the sludge, allowing the excess free water in the high-water content sludge to secrete out, accelerating the dehydration of the high-water content sludge, and preventing excessive water content from affecting the solidification strength of the cementing material on the sludge particles. Sodium polyacrylate has extremely strong water absorption, can quickly absorb excess water in the high-water content sludge, accelerate the dehydration of the high-water content sludge, and form a gel material, which has a cementing effect on the sludge particles, and is conducive to the rapid solidification of the high-water content sludge.

[0036] In some embodiments, the bentonite is sodium bentonite; the polyacrylamide is anionic polyacrylamide. When sodium bentonite, anionic polyacrylamide and sodium polyacrylate are added to the binder of high-water content sludge at the same time, a complex polymerization reaction will occur in the alkaline environment formed after quicklime hydration. On the one hand, the sodium ions in the sodium bentonite will undergo ion exchange with the anionic groups in the anionic polyacrylamide, and the carboxyl groups of sodium polyacrylate will undergo ion exchange with the sodium ions between the bentonite layers. The above reactions will cause the interlayer spacing of the bentonite to change, which is conducive to the looser structure of the bentonite, convenient for the entry and adsorption of water molecules, and improve the water absorption of the bentonite, which is more conducive to the rapid dehydration of the high-water content sludge. On the other hand, the tiny flakes of bentonite can adsorb anionic polyacrylamide molecular chains and sodium polyacrylate colloidal particles, and anionic polyacrylamide molecular chains and sodium polyacrylate can attract each other through electrostatic effects, hydrogen bonds and van der Waals forces to form a complex network structure. When combined with bentonite, a more complex three-dimensional spatial network of surface-network-surface will be formed, which is conducive to locking silt particles and forming firm aggregates, thereby improving the curing strength of the cementitious material.

[0037] In some embodiments, the mass ratio of the polyacrylamide to the sodium polyacrylate is (1-2): 1; the mass ratio of the bentonite to the anti-dispersant is (4-5): 1. Within the above range, the water absorption of the bentonite can be improved, rapid dehydration can be achieved, and the curing strength of the cementing material can be improved.

[0038] In some embodiments, the modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 140℃~160℃ for 0.5h~1h to obtain modified papermaking black liquor.

[0039] Preferably, the papermaking black liquor is the papermaking black liquor produced in the alkaline pulping process; the concentration of the high-concentration papermaking black liquor is 60% to 70%.

[0040] It should be noted that, in the alkaline pulping process, the cellulose in the papermaking raw material is utilized and made into a finished product, and the lignin in the papermaking raw material is degraded and dissolved in the cooking liquid in the form of lignin sodium salt. In this way, alkaline lignin, hemicellulose and residual alkali constitute the main components of black liquor. A large amount of black liquor is not treated or is directly discharged into the environment after simple treatment, which will cause serious pollution to the environment. The present invention evaporates and concentrates the papermaking black liquor and performs sulfonation modification to obtain a high-concentration modified papermaking black liquor. The modified papermaking black liquor contains lignin sulfonate, which can make the raw materials of the binder material disperse more evenly and is conducive to dehydration and solidification. Further, the lignin sulfonate in the modified papermaking black liquor undergoes a graft copolymerization reaction with polyacrylamide under the stimulation of alkaline conditions, and the copolymerization product can condense the tiny particles in the sludge into larger particles, and can also fill the pores in the sludge to form a more compact bonding structure, thereby enhancing the bonding strength of the sludge, making it easier to solidify and handle.

[0041] Accordingly, the present invention also provides a method for preparing a cementing material for high-water content sludge, comprising the following steps:

[0042] In parts by weight, 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite and 0.5-4 parts of anti-dispersant are mixed to obtain a binder material for high-water content sludge.

[0043] In some embodiments, the mixing process is performed at a stirring rate of not less than 50 revolutions per second.

[0044] And, the application of the above-mentioned cementing material for high-water content sludge in the solidification of high-water content sludge. In some embodiments, the cementing material for high-water content sludge is added to the sludge at a dosage of 4% to 6%; the cementing material for high-water content sludge and the sludge are evenly mixed and dehydrated and solidified; the dehydrated and solidified sludge is tested and applied to the fields of base filling and the like.

[0045] The present invention is further described below with reference to specific embodiments.

[0046] Example 1

[0047] This embodiment provides a cementing material for high-water content sludge, which includes the following components by weight: 30 parts of silicate cement, 35 parts of lime, 20 parts of fly ash, 6 parts of modified papermaking black liquor, 15 parts of anionic bentonite, 2 parts of polyacrylamide, and 1 part of sodium polyacrylate;

[0048] The modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 150°C for 0.5h to obtain modified papermaking black liquor.

[0049] Example 2

[0050] The present embodiment provides a binder material for high-water content sludge, which includes the following components in parts by weight: 25 parts of Portland cement, 35 parts of lime, 25 parts of fly ash, 6 parts of modified papermaking black liquor, 10 parts of anionic bentonite, 1 part of polyacrylamide, and 1 part of sodium polyacrylate.

[0051] The modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 150°C for 0.5h to obtain modified papermaking black liquor.

[0052] Example 3

[0053] The present embodiment provides a binder material for high-water content sludge, which includes the following components in parts by weight: 25 parts of silicate cement, 40 parts of lime, 20 parts of fly ash, 6 parts of modified papermaking black liquor, 20 parts of anionic bentonite, 2 parts of polyacrylamide, and 2 parts of sodium polyacrylate.

[0054] The modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 150°C for 0.5h to obtain modified papermaking black liquor.

[0055] Example 4

[0056] The present embodiment provides a binder material for high-water content sludge, which includes the following components in parts by weight: 29 parts of silicate cement, 35 parts of lime, 20 parts of fly ash, 6 parts of modified papermaking black liquor, 12 parts of anionic bentonite, 2 parts of polyacrylamide, and 1 part of sodium polyacrylate.

[0057] The modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 150°C for 0.5h to obtain modified papermaking black liquor.

[0058] Example 5

[0059] The present embodiment provides a binder material for high-water content sludge, which includes the following components in parts by weight: 29 parts of silicate cement, 30 parts of lime, 20 parts of fly ash, 6 parts of modified papermaking black liquor, 16 parts of anionic bentonite, 2 parts of polyacrylamide, and 2 parts of sodium polyacrylate.

[0060] The modified papermaking black liquor is prepared by the following method: the papermaking black liquor is evaporated and concentrated to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 150°C for 0.5h to obtain modified papermaking black liquor.

[0061] Comparative Example 1

[0062] This comparative example provides a binder material for high-water content sludge, which includes the following components in parts by weight: 30 parts of Portland cement, 35 parts of lime, 20 parts of fly ash, 15 parts of anionic bentonite, and 1 part of sodium polyacrylate.

[0063] Comparative Example 2

[0064] This comparative example provides a binder material for high-water content sludge, which includes the following components in parts by weight: 30 parts of Portland cement, 35 parts of lime, 20 parts of fly ash, 15 parts of anionic bentonite, and 2 parts of polyacrylamide.

[0065] Comparative Example 1

[0066] This comparative example provides a binder material for high-water content sludge, which includes the following components in parts by weight: 30 parts of Portland cement, 35 parts of lime, 20 parts of fly ash, 2 parts of polyacrylamide, and 1 part of sodium polyacrylate.

[0067] Comparative Example 2

[0068] This comparative example provides a cementing material for high-water content sludge, which includes the following components by weight: 30 parts of silicate cement, 35 parts of lime, 20 parts of fly ash, 15 parts of anionic bentonite, 2 parts of polyacrylamide, and 1 part of sodium polyacrylate.

[0069] The test soil was river dredged silt, which had a moisture content of 92% and an organic matter content of 8.3%. The amount of binder used for high-moisture-content silt during molding was 5% of the mass of the dredged silt.

[0070] During the test, the CBR and unconfined compressive strength molding and testing were carried out in accordance with the method specified in the "Highway Geotechnical Test Code" (JTG 3420-2020), and the loss of unconfined compressive strength under immersion conditions was tested to judge the water resistance of the dredged silt solidified soil. The test results of Examples 1 to 5, Comparative Examples 1 to 2 and Comparative Examples 1 to 2 are shown in Table 1.

[0071] Table 1 Test results of Examples 1 to 5, Comparative Examples 1 to 2 and Comparative Examples 1 to 2

[0072]

[0073] As can be seen from Table 1, by comparing Examples 1 to 5 with Comparative Example 1, Comparative Example 2, Comparative Example 1, and Comparative Example 2, it can be seen that the addition of specific types of bentonite, anti-dispersant, and modified papermaking black liquor can play a vital role in improving the CBR and unconfined compressive strength of solidified dredged silt soil. The cementing materials for resource processing of high-water content dredged silt provided in Examples 1 to 5 have a much better solidification effect on dredged silt than the solidification effect of traditional cement and lime. The cementing materials for resource processing of high-water content dredged silt in this embodiment have an excellent solidification effect on dredged silt, and can be applied to the solidification treatment of high-water content and high-organic dredged silt. The dredged silt after solidification can be used for foundation backfill, roadbed filling and other projects, which is beneficial to the treatment and resource utilization of dredged silt and reduces pollution to the environment.

[0074] In the description of this specification, the description with reference to the terms "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0075] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A cementing material for high-water content sludge, characterized in that: The invention comprises the following components in parts by weight: 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite and 0.5-4 parts of anti-dispersant.

2. The cementing material for high-water content sludge according to claim 1, characterized in that: The anti-dispersion agent includes polyacrylamide and sodium polyacrylate.

3. The cementing material for high-water content sludge according to claim 2, characterized in that: The mass ratio of the polyacrylamide to the sodium polyacrylate is (1-2):

1.

4. The cementing material for high-water content sludge according to claim 2, characterized in that: The bentonite is sodium bentonite; The polyacrylamide is anionic polyacrylamide.

5. The cementing material for high-water content sludge according to claim 4, characterized in that: The mass ratio of the bentonite to the anti-dispersant is (4-5):

1.

6. The cementing material for high-water content sludge according to claim 1, characterized in that: The modified papermaking black liquor is prepared by the following method: Evaporating and concentrating papermaking black liquor to obtain high-concentration papermaking black liquor; Na2SO3 is added to the high-concentration papermaking black liquor and reacted at 140°C to 160°C for 0.5h to 1h to obtain modified papermaking black liquor.

7. The cementing material for high-water content sludge according to claim 6, characterized in that: The papermaking black liquor is the papermaking black liquor produced in the alkaline pulping process; The concentration of the high-concentration papermaking black liquor is 60% to 70%.

8. The cementing material for high-water content sludge according to claim 1, characterized in that: The strength grade of the silicate cement is not less than 42.5; The lime is quicklime, and the effective CaO content is not less than 85%; The fly ash is Class II fly ash.

9. A method for preparing a cementing material for high-water content sludge according to any one of claims 1 to 8, characterized in that: In parts by weight, 25-40 parts of silicate cement, 30-45 parts of lime, 15-30 parts of fly ash, 5-10 parts of modified papermaking black liquor, 10-25 parts of bentonite and 0.5-4 parts of anti-dispersant are mixed to obtain a binder material for high-water content sludge.

10. Use of the binder material for high-water-content sludge according to any one of claims 1 to 8 in solidification of high-water-content sludge.

Citation Information

Patent Citations

  • Curing agent for heavy-metal polluted bottom sludge

    CN102503274A

  • Compound curing agent for dredged silt and preparation method thereof

    CN107226661A

  • Silt hardening agent and preparation method and application method thereof

    CN107522436A

  • Low-alkalinity environment-friendly curing agent for river and lake desilting sediment and using method thereof

    CN112321262A

  • Preparation method of phosphogypsum-based cement admixture

    CN114685080A